Anne Frank, beyond the diary : a photographic remembrance - Rol, Ruud van der; Verhoeven, Rian; Anne Frank Stichting (Viking, 1993)
Photographs, illustrations, and maps accompany historical essays, diary excerpts, and interviews, providing an insight to Anne Frank and the massive upheaval which tore apart her world